Analysis of experience and efficiency of distance learning master’s degree programme in construction economics and property management - Rimkuviene, Silva; Lepkova, Natalija (Journal of Civil Engineering and Management, 2004)
This paper reviews the distance learning development in the world and in Lithuania. Nine years of theoretical and practical experience of distance learning under two study programmes at the Department of Construction Economics and Property Management at Vilnius Gediminas Technical University is presented. These masters degree study programmes were one of the first in Central and Easten Europe. According to the questionnaire of both former and current students, the findings of this poll are analysed. Mostly there were employees from real estate sector and construction enterprises questioned. The conclusions are drawn, emphasising the problems of learning process. In addition, social, economical, technological, and ethical points are analysed as well as the problem of the integration of trained professionals into the market. First Published Online: 14 Oct 2010